"Anne Rice for Kids" and Twilight for TV: Young Adult Media Franchising and the Vampire Diaries - (:unkn) unknown (My University, 2015)
This thesis examines The Vampire Diaries as representative of the contemporary state of feminized media franchises, especially those that address young women. The Vampire Diaries exists primarily as a book series and a television series, produced by Alloy Entertainment and The CW Network respectively. Alloy’s production of the franchise, and others like it, connects to the company’s history of feminized media production as a book packager, and is indicative of its current transmedia consumerist model. Further, it underlines the importance of trends and the problematic role of the author in YA literature. The CW’s use of franchises like The Vampire Diaries has helped them create a brand as a new network, one that builds on the history of its predecessor, the WB, but adjusted to reach consumers of teen media newly configured as Millennials. By developing digital strategies to reach a feminine, Millennial audience, such as streaming availability, exclusive digital content, and engaging social media, the CW has become an innovator within the contemporary franchise model.
Keywords: Franchising; Media Industry; Millennials; Teen Media; Television; Young Adult Literature